Typy uczniów w młodszym wieku szkolnym a ich strategie uczenia się i preferencje – doniesienia z badań - Skibska, Joanna (Studia Edukacyjne, 2020)
The article presents findings of the research on the diagnosis of student types and strategies and techniques of learning preferred by students with very good performance in learning, as well as those with learning disabilities and special educational needs (SEN). Research reveals the occurrence of certain regularities in individual student groups. Students with high learning outcomes are primarily of an intellectual type and prefer visual learning strategies, whereas students with learning disabilities are of an emotional, acting and cooperating type, their learning based on auditory and kinesthetic strategies. Students with special educational needs are of an emotional type. Hence, they most often use auditory and visual learning strategies. In the individual groups, there a marked correlation was observed between the student types and professional preferences. The intellectual type (students with high scores) would like to engage in occupations related to intellectual and artistic work in the future; the emotional, acting and cooperating type (children with learning difficulties) is interested in performing service professions, while the emotional type (students with special educational needs) sees their future in counselling professions.